IMPLEMENTATION OF THE TOURISM CODE OF ETHICS IN THE CANGGU TOURISM AREA TO SUPPORT SUSTAINABLE TOURISM PROGRAMS IN BADUNG REGENCY - Maria Bertila Bere (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study examines the implementation of the Tourism Code of Ethics in the Canggu tourism area to support sustainable tourism in Badung Regency. It addresses three main issues: (1) the types of tourism codes of ethics applied, (2) the strategies used in their implementation, and (3) the implications of these practices for sustainable tourism. The study also evaluates how the code of ethics regulates interactions among tourists, tourism industry actors, and local communities, as well as its contribution to mitigating negative impacts such as environmental degradation, cultural disruption, and social imbalance, particularly in the context of overtourism. This research employs a qualitative descriptive method, with data collected through field observations, stakeholder interviews, and literature review. The data were analyzed to assess the effectiveness of ethical practices in supporting sustainable tourism. The findings reveal that: (1) the implementation of tourism codes of ethics, including waste separation, use of local products, and respect for local customs, promotes responsible behavior among tourists and industry actors, helping maintain environmental and cultural balance; (2) collaborative strategies developed through regular interactions among village governments, accommodation providers, MSMEs, and customary communities effectively reduce social conflicts, strengthen the local economy, and enhance cultural awareness among tourists; and (3) active community involvement in tourism activities, such as traditional cooking classes, cultural performances, and local guiding, increases community income, fosters cultural pride, strengthens host-guest relationships, and functions as an educational medium for visitors.